Discover the answers you need at Westonci.ca, a dynamic Q&A platform where knowledge is shared freely by a community of experts. Connect with professionals on our platform to receive accurate answers to your questions quickly and efficiently. Get detailed and accurate answers to your questions from a dedicated community of experts on our Q&A platform.
Sagot :
Let's carefully examine each step of solving the system of linear equations to determine where Michael made his first error.
We start with the system of equations:
[tex]\[ \begin{aligned} 3x - 3y &= 6 \quad \text{(Equation 1)}\\ 4x - 7y &= 2 \quad \text{(Equation 2)} \end{aligned} \][/tex]
Step 1: Multiply the equations to eliminate [tex]\( x \)[/tex].
Multiply Equation 1 by 4:
[tex]\[ 4(3x - 3y) = 4(6) \implies 12x - 12y = 24 \][/tex]
Multiply Equation 2 by -3:
[tex]\[ -3(4x - 7y) = -3(2) \implies -12x + 21y = -6 \][/tex]
This step is correct. Let's move on to Step 2.
Step 2: Add the two equations to eliminate [tex]\( x \)[/tex].
[tex]\[ \begin{aligned} 12x - 12y &= 24 \quad \text{(Equation 3)}\\ -12x + 21y &= -6 \quad \text{(Equation 4)} \end{aligned} \][/tex]
Adding Equation 3 and Equation 4:
[tex]\[ (12x - 12y) + (-12x + 21y) = 24 + (-6) \implies 9y = 18 \][/tex]
This step should yield:
[tex]\[ 9y = 18 \implies y = 2 \][/tex]
Michael, however, showed:
[tex]\[ -33y = 30 \][/tex]
This means Michael made an error in Step 2.
Given that:
- The incorrect intermediate value for [tex]\( y \)[/tex] was [tex]\( -\frac{10}{11} \)[/tex],
- The correct value for [tex]\( y \)[/tex] from the corrected steps is [tex]\( 2 \)[/tex],
- The correct further substitution for [tex]\( x \)[/tex],
The error occurred in Step 2 when combining Equations 3 and 4. Therefore, Michael's first error happened in Step 2.
We start with the system of equations:
[tex]\[ \begin{aligned} 3x - 3y &= 6 \quad \text{(Equation 1)}\\ 4x - 7y &= 2 \quad \text{(Equation 2)} \end{aligned} \][/tex]
Step 1: Multiply the equations to eliminate [tex]\( x \)[/tex].
Multiply Equation 1 by 4:
[tex]\[ 4(3x - 3y) = 4(6) \implies 12x - 12y = 24 \][/tex]
Multiply Equation 2 by -3:
[tex]\[ -3(4x - 7y) = -3(2) \implies -12x + 21y = -6 \][/tex]
This step is correct. Let's move on to Step 2.
Step 2: Add the two equations to eliminate [tex]\( x \)[/tex].
[tex]\[ \begin{aligned} 12x - 12y &= 24 \quad \text{(Equation 3)}\\ -12x + 21y &= -6 \quad \text{(Equation 4)} \end{aligned} \][/tex]
Adding Equation 3 and Equation 4:
[tex]\[ (12x - 12y) + (-12x + 21y) = 24 + (-6) \implies 9y = 18 \][/tex]
This step should yield:
[tex]\[ 9y = 18 \implies y = 2 \][/tex]
Michael, however, showed:
[tex]\[ -33y = 30 \][/tex]
This means Michael made an error in Step 2.
Given that:
- The incorrect intermediate value for [tex]\( y \)[/tex] was [tex]\( -\frac{10}{11} \)[/tex],
- The correct value for [tex]\( y \)[/tex] from the corrected steps is [tex]\( 2 \)[/tex],
- The correct further substitution for [tex]\( x \)[/tex],
The error occurred in Step 2 when combining Equations 3 and 4. Therefore, Michael's first error happened in Step 2.
Thanks for using our platform. We aim to provide accurate and up-to-date answers to all your queries. Come back soon. We appreciate your time. Please revisit us for more reliable answers to any questions you may have. Westonci.ca is here to provide the answers you seek. Return often for more expert solutions.